Oral Squamous Cell Carcinoma in a Young Female Without Risk Factors: An Uncommon Clinical Presentation - Tandon, Sapna; Kumari , Payal; Bansal , Muskan; Chauhan , Himanshu; Mehra, Hemant; Kumar , Aakash (Journal of Neonatal Surgery, 2025)
Background: Oral squamous cell carcinoma (OSCC) is the most prevalent type of oral cancer, constituting nearly 90% of all oral malignancies. It typically affects individuals above the age of 30 and is strongly associated with risk factors such as tobacco, alcohol, areca nut, and chronic sun exposure. However, its presentation in younger individuals, particularly females without deleterious habits, remains rare and often overlooked in early stages. Case Report: We report a rare case of OSCC in a 24-year-old female with no history of tobacco, alcohol use, or systemic illness. The patient presented with a progressively enlarging, erythematous, exophytic growth in the left mandibular posterior region, following a history of grossly decayed tooth (tooth - 37) seven months prior. Clinical examination revealed a lobulated lesion measuring approximately 2.5 × 3.0 cm, with associated left submandibular lymphadenopathy. CBCT imaging revealed an ill-defined radiolucency with cortical plate destruction and close approximation to the inferior alveolar canal. A provisional diagnosis of OSCC was made, and biopsy was advised. OSCC is confirmed by the histopathological examination. Conclusion: This rare case highlights that OSCC may arise in young individuals without traditional risk factors, underscoring the importance of clinical vigilance. Any persistent or unexplained oral lesion should be promptly investigated through thorough examination and biopsy. Early recognition and intervention are crucial to achieving better prognosis and functional outcomes.